African economic community treaty : issues, problems, and prospects - Ajomo, M. Ayo.; Adewale, Omobolaji (Lagos : Nigerian Institute of Advanced Legal Studies, 1993)
This publication comprise of papers delivered at the International Conference on African Economic Community Treaty held at Abuja from January 27-30, 1992
Includes bibliographical references and index.
lje 27/07/2016
Loans
Keywords: International economic cooperation; Economic treaty; Economic community - Africa; Africa